Effect of Addition of Methionine to Rice Protein on the Cholesterol and Lipoproteins Concentrations in Rats - Jaefar Dhahir; Jaber Dhahir; Qassem Al-Awwad (مجلة جامعة الانبار للعلوم الصرفة, 2012)
The effect of the addition of methionine to rice protein on the levels of plasma and lipoproteins cholesterol in relation to the casein were investigated in rats. Rats were fed diets containing casein (C), rice protein (RP), casein and colfibrate (CC), and rice protein with methionine (RPM). Serum total cholesterol concentrations were lower in rats fed RP, CC, and RPM diets than those fed C diet. The concentration of liver cholesterol was also lower in rats fed the RP diet.The serum high density lipoprotein (HDL) cholesterol level and fecal bile acids were higher in rats fed (RP) diet than in those fed (C) or RPM diets.These results indicated that increased fecal bile acids excretion may be responsible for the antihypercholesterolemic effect of rice protein compared with casein.